2010
DOI: 10.1007/s00520-010-0889-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral risk factors and use of preventive screening services among spousal caregivers of cancer patients

Abstract: Although spousal caregivers of cancer patients were more likely to use cancer screening services, their health behavior with regard to other aspects were not different from controls. There is a need to improve other types of health behaviors, especially lifestyle behavior, and balance these with cancer screenings in caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 26 publications
1
38
1
3
Order By: Relevance
“…Furthermore, significantly less proportion of caregivers was estimated as being physically active (16%) when compared to the controls from KNHANES V (29.1%). This is different from the results of Son et al (2011) study, which demonstrated no difference in physical activity between spousal caregivers and controls from KNHANES III (23.1% vs. 15%). Comparison of physical activity of caregivers and non-caregivers who were not regular exercisers demonstrated no difference in physical activities (Marquez et al, 2012).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Furthermore, significantly less proportion of caregivers was estimated as being physically active (16%) when compared to the controls from KNHANES V (29.1%). This is different from the results of Son et al (2011) study, which demonstrated no difference in physical activity between spousal caregivers and controls from KNHANES III (23.1% vs. 15%). Comparison of physical activity of caregivers and non-caregivers who were not regular exercisers demonstrated no difference in physical activities (Marquez et al, 2012).…”
Section: Discussioncontrasting
confidence: 84%
“…However, Korean spousal caregivers' better compliance to cancer screening guidelines has been demonstrated by Son et al (2011). Caregivers in this study also demonstrated better cancer screening adherences in terms of receiving stomach, breast, and cervical cancer screening tests than controls from the KNHANES V. The impact of family member's cancer diagnosis toward health-promoting behavior could serve as possible explanation (Humpel et al, 2007;Lemon et al, 2004).…”
Section: Discussionmentioning
confidence: 45%
“…Studies from other countries also pointed out similar findings (Humpel et al, 2007;Son et al, 2011).…”
Section: Discussionsupporting
confidence: 63%
“…Six studies focused on caregivers of patients with multiple forms of cancer. 41,4347 Two studies focused specifically on caregivers of individuals with ovarian 42 and breast cancer. 48 Cancer stage was reported in 4 of the studies.…”
Section: Resultsmentioning
confidence: 99%
“…4247 The remaining 2 studies reported at least 1 health behavior as it related to another primary outcome (eg, alcohol use as an avoidant coping behavior). 41,48 …”
Section: Resultsmentioning
confidence: 99%